1979
DOI: 10.1139/v79-297
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-induced changes in 2J(H, F) for fluoroform via van der Waals interactions. Non-contact contributions to spin–spin coupling constants involving a proton?

Abstract: . Can. J. Chem. 57, 1877 (1979). The spin-spin coupling between the proton and the fluorine nuclei, 'J, in fluoroform varies by 1% in a range of solvents. It is argued that 'J decreases algebraically as the van der Waals solute-solvent interactions increase in magnitude. Such a decrease is also observed for coupling constants which likely contain a substantial positive orbital contribution. If the van der Waals interactions perturb the spin-orbital term in J , then 'J in fluoroform may well contain orbital con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Recently, Schaefer et al [33] found experimental evidences that would indicate the presence of interaction mechanisms of the noncontact types in couplings involving protons. Therefore, at present, it seems to be of some importance to study more thoroughly these mechanisms, and in particular, to revise the validity of the McConnell approximation 1231.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schaefer et al [33] found experimental evidences that would indicate the presence of interaction mechanisms of the noncontact types in couplings involving protons. Therefore, at present, it seems to be of some importance to study more thoroughly these mechanisms, and in particular, to revise the validity of the McConnell approximation 1231.…”
Section: Discussionmentioning
confidence: 99%